Implementing pharmacogenetic testing in community pharmacy practice: a scoping review - Coumau, Aude; Coumau, Claire; Csajka, Chantal (Frontiers in Pharmacology, 2025)
The field of pharmacogenetics (PGx) has expanded significantly in recent years, with growing evidence supporting its role in enhancing medication effectiveness and reducing adverse drug events. Yet, the integration of PGx into routine clinical practice remains limited. Community pharmacies hold a key position in the healthcare system, offering expert medication advice and maintaining close patient contact due to their accessibility. This context has driven research efforts to integrate PGx testing into healthcare systems in various countries. However, evidence on optimal strategies for embedding PGx services in community pharmacy settings is still emerging. We conducted a scoping review to provide a comprehensive overview of the implementation of PGx testing in community pharmacies, focusing on both successful strategies and challenges. A systematic search of studies involving PGx testing in community pharmacies was conducted using PubMed, Embase, the Cochrane Library and Web of Science, including all publications up to February 2025. The search considered implementation outcomes: feasibility, acceptability, adoption, fidelity, appropriateness, cost, penetration and sustainability. The process and reporting followed the PRISMA recommendations for scoping reviews (PRISMA-ScR). Study findings were classified according to Proctor’s implementation outcomes. A total of 17 studies met the inclusion criteria and were included in the review. Key implementation variables were extracted from these studies. Feasibility was supported by a manageable time process and high technical success. The appropriateness of PGx was reflected in its ability to identify numerous medication-related issues. Adoption varied between patients and prescribers. While patient engagement was high, many sharing PGx results with other physicians, integration of PGx recommendations by prescribers was inconsistent. The intervention was generally well accepted, with high satisfaction among patients and pharmacists, although some physicians expressed concerns. These findings illustrate potential approaches to implementing PGx testing in community pharmacy settings. This scoping review demonstrates the potential for PGx testing to become a viable part of routine care in community pharmacies. It highlights positive patient perceptions and provider willingness to adopt testing. However, it also identifies key barriers, including the need for standardized PGx guidelines, education for providers, and reimbursement policies. The study underscores the importance of patient education, seamless integration into pharmacy workflows, and continued research to support successful implementation.